Review of Legal Protection of Indonesia in Australia Tapping Case - Hanna Wijaya; Yohanes Firmansyah; Yana Sylvana; Michelle Angelika S (International Journal of Social Science and Religion (IJSSR), 2022)
Several facts show that Australia has done several times wiretapping efforts against Indonesia. It is generally known that action tapping is an act of collecting information in secret diplomatic relations of a country. This journal is meant for analyzing the principle of the prohibition of wiretapping in the National Law, legal protection, and legal remedies that can be taken by Indonesia in the case of wiretapping. The research method used in this study is juriditve normative. This research analyzes relevant international treaties, case approaches, legal concept analysis approaches, and comparative approaches. The results of the study legally tapping is prohibited by law and international human rights based on the Universal Declaration of Human Rights (UDHR) in 1948, the International Covenant on Civil and Political Rights (ICCPR) in 1966, the European Convention for the Protection of Human Rights and Fundamental Freedoms (1958) and the 1961 Vienna Convention. While in the national law, the prohibition of tapping is provided in Article 28G paragraph (1) of the 1945 Constitution, Article 32 of law No. 39 of 1999, Article 40 of Law No. 36 of 1999, Article 31 paragraph (1) of Law No. 11 of 2008, and Article 31 paragraph (2) of Law No. 11 the Year 2008. concluded, juridically tapping is an act prohibited under international law and human rights In international law, Indonesian national law prohibits wiretapping. Indonesia has signed the Code of Conduct on Framework for Security Cooperation to prevent wiretapping. Besides, Indonesia can also bring wiretapping cases to the International Court of Justice because the Defense Signals Directorate (DSD) is the Australian government's official intelligence agency. The behavior of relations between countries and tapping as done by Australia to Indonesia appears to have shifted the meaning no longer as a crime but rather a violation of the diplomatic code of ethics.